Accuracy and Safety of Novel Designs for Phase I Drug-Combination Oncology Trials. (3rd August 2022) - Liu, Rong; Yuan, Ying; Sen, Suman; Yang, Xin; Jiang, Qi; Li, Xiaoyun (Nicole); Lu, Chengxing (Cindy); Gönen, Mithat; Tian, Hong; Zhou, Heng; Lin, Ruitao; Marchenko, Olga
ABSTRACT: Despite numerous innovative designs having been published for phase I drug-combination dose finding trials, their use in real applications is rather limited. As a working group under the American Statistical Association Biopharmaceutical Section, our goal is to identify the unique challenges associated with drug combination, share industry's experiences with combination trials, and investigate the pros and cons of the existing designs. Toward this goal, we review seven existing designs and distinguish them based on the criterion of whether their primary objectives are to find a single maximum tolerated dose (MTD) or the MTD contour (i.e., multiple MTDs). Numerical studies, based on either industry-specified fixed scenarios or randomly generated scenarios, are performed to assess their relative accuracy, safety, and ease of implementation. We show that the algorithm-based 3 + 3 design has poor performance and often fails to find the MTD. The performance of model-based combination trial designs is mixed: some demonstrate high accuracy of finding the MTD but poor safety, while others are safe but with compromised identification accuracy. In comparison, the model-assisted designs, such as BOIN and waterfall designs, have competitive and balanced performance in the accuracy of MTD identification and patient safety, and are also simple to implement, thus offering an attractive approach to designing phase I drug-combination trials. By taking into consideration the design's operating characteristics, ease of implementation and regulation, the need for advanced infrastructures, as well as the risk of regulatory acceptance, our article offers practical guidance on the selection of a suitable dose-finding approach for designing future combination trials.